Peranan Manajemen Berbasis Sekolah (MBS) - Maman Mulya Karnama; Depi Prihamdani (Jurnal Sekolah Dasar, 2019)
The development of Science and Technology has an impact on major changes that occur in the world of education. One of the fundamental changes in the world of education is at the management level, from central-based management to regional-based management. The method used in this paper is only based on literature review / literature, so to find out the role of implementing School-based Management (MBS) in teaching and learning in schools, will be reviewed and reviewed based on facts and opinions from experts who are competent in the field of education.